2021
DOI: 10.18844/cjes.v16i4.6053
|View full text |Cite
|
Sign up to set email alerts
|

Formation of professional competence of learners in teaching medicinal plants

Abstract: Professional competence is a necessary component of a person's professionalism in any area. The aim of the research is the formation of the professional activity of a future competitive specialist in the educational process of universities for the system-structural organization of professional training of biology students. The analysis of a wide range of various works aimed at professional pedagogical training of future specialists leads to the conclusion that its structure, content and organization can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…When examining studies related to medicinal and economic plants, it is generally observed that research focuses on the medicinal plants of specific geographical regions, cities, or provinces (YÖK, 2023). Taking into account the pre-test score of 29 and post-test scores of 87, it is observed that the results of this study overlap with Kassimbekova et al (2021). Similarly, Brandão et al (2023) emphasized the importance of medicinal plants and the necessity of teaching them to students in their study "Teaching Medicinal Plants at School: In the Footsteps of Frei Veloso".…”
Section: Discussionmentioning
confidence: 66%
“…When examining studies related to medicinal and economic plants, it is generally observed that research focuses on the medicinal plants of specific geographical regions, cities, or provinces (YÖK, 2023). Taking into account the pre-test score of 29 and post-test scores of 87, it is observed that the results of this study overlap with Kassimbekova et al (2021). Similarly, Brandão et al (2023) emphasized the importance of medicinal plants and the necessity of teaching them to students in their study "Teaching Medicinal Plants at School: In the Footsteps of Frei Veloso".…”
Section: Discussionmentioning
confidence: 66%